Analisis Konsep Poligami dalam Al-Qur’an (Studi Tafsir AL-Misbah oleh M. Quraish Shihab) - Siti Asiyah; Rakhmat Rakhmat; Habib Ismail; Ari Rohmawati (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2018)
The polemic about polygamy is increasingly prominent and attracts attention when the practice of polygamy is openly carried out by public figures ranging from entrepreneurs, politicians, scholars, to comedians. Even the conversation about polygamy never seems to stop. Recently, conversations have turned into interesting debates, especially since the post-New Order era. Polygamy was